2012
DOI: 10.1186/2046-0481-65-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defence of colostrum and milk in consecutive lactations in sows

Abstract: BackgroundParturition is supposed to be related to oxidative stress, not only for the mother, but also for the newborn. Moreover, it is not clear whether consecutive pregnancies, parturitions, and lactations are similar to each other in regards to intensity of metabolic processes or differ from each other. The aim of the study was to compare dynamic changes of antioxidative parameters in colostrum and milk of sows taken during 72 h postpartum from animals in consecutive lactations. Activities of glutathione pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Oxidative stress is adverse to milk yield, health and litter performance (Kim, Weaver, Shen, & Zhao, 2013; Lipko‐Przybylska & Kankofer, 2012). The gestation and lactation are always accompanied by increasing systemic oxidative stress (Berchieri‐Ronchi et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is adverse to milk yield, health and litter performance (Kim, Weaver, Shen, & Zhao, 2013; Lipko‐Przybylska & Kankofer, 2012). The gestation and lactation are always accompanied by increasing systemic oxidative stress (Berchieri‐Ronchi et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the above, gestation, the perinatal period, weaning (Fan et al 2015), and high stocking density in commercial farms where pigs are kept on slatted floors are sources of considerable stress for animals. These factors lead to a rapid increase in the concentrations of reactive oxygen species (ROS) and induce oxidative stress (Frankic and Salobir 2011;Lipko-Przybylska and Kankofer 2012;Durand et al 2013). The resulting redox imbalance can induce irreversible structural and functional changes in cells, including DNA damage, amino acid modification, protein fragmentation, lipid peroxidation in cell membranes, apoptosis and cell necrosis (Lykkesfeldt and Svendsen 2007;Lipi nski et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The level of vitamin C in the experimental group (both in colostrum and milk) was higher as compared with the control group (P ≤ 0.01). Other authors (15) reported that the concentration of vitamin C was the highest between the 18 th and 36 th h postpartum.…”
Section: Resultsmentioning
confidence: 95%